The Influence of Tourist Expectations on Tourist Loyalty in Henan, China: Mediated by Tourist Perceptions and Satisfaction - Ge, Jinbao; Huang, Yue (Rajapark Journal, 2025)
Tourism is a vital driver of regional economies, and Henan Province, with its rich historical and cultural heritage, faces intensifying competition in China’s tourism market. Understanding how tourist expectations affect loyalty is essential for sustainable development. This study aimed to examine: 1) the direct impact of tourist expectations on tourist loyalty, as well as on perceived quality, perceived value, and satisfaction; 2) how perceived quality and perceived value influence tourist satisfaction, and how satisfaction in turn affects tourist loyalty; and 3) the mediated roles of perceived quality, perceived value, and satisfaction in the relationship between tourist expectations and tourist loyalty. A quantitative design was employed using structural equation modeling (SEM). Data were obtained from 400 valid questionnaires collected from Chinese tourists visiting Henan between March and May 2025. Survey items covered six dimensions of tourism services-food, hotel, transportation, scenery, shopping, and recreation—and were analyzed using SPSS 27.0 and AMOS 28.0. Results show that expectations positively affect loyalty (β=0.64, p<0.001), perceived quality (β=0.46, p<0.001), and perceived value (β=0.36, p<0.001), but negatively influence satisfaction (β=-0.46, p<0.001). Perceived quality (β=0.52, p<0.001) and perceived value (β=0.17, p<0.01) both enhance satisfaction, which significantly predicts loyalty (β=0.33, p<0.001). Mediation tests confirm that perceived quality and satisfaction partially mediate the effects of expectations on loyalty, while excessive expectations may lower satisfaction through disconfirmation. The findings extend expectation-disconfirmation theory and highlight the importance of aligning marketing communication with realistic service standards. For Henan, strengthening service quality in the six key areas and managing pre-travel information can improve satisfaction and foster long-term tourist loyalty.